The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fmars.2021.689998
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Limitations of Marine Synechococcus Blue-Green Chromatic Acclimation

Abstract: Benefits and trade-offs of blue/green chromatic acclimation (CA4) have received limited study. We investigated the energetic costs associated with executing chromatic acclimation using a fluorescence-based calculation of light use efficiency. Using laboratory cultures and artificial light environments, we show that the delayed response to acclimation known to occur in marine Synechococcus acclimating strains (generalists) in green light do not reduce light use efficiency in green light, but that only one gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…1). In this context, (Lovindeer et al, 2021) also recently showed that CA4-capable Synechococcus strains were characterized by much higher light use efficiency in GL than in BL, often associated with faster growth rate. The latter difference with our results can be explained by the fact that the blue LEDs used in this previous study had a peak at 440 nm, mainly absorbed by Chl a (Amax = 440 nm) but very poorly by PUB (Amax = 495 nm), resulting in strong limitation of the production of chemical energy by photosynthesis in their BL condition.…”
Section: Discussionmentioning
confidence: 91%
“…1). In this context, (Lovindeer et al, 2021) also recently showed that CA4-capable Synechococcus strains were characterized by much higher light use efficiency in GL than in BL, often associated with faster growth rate. The latter difference with our results can be explained by the fact that the blue LEDs used in this previous study had a peak at 440 nm, mainly absorbed by Chl a (Amax = 440 nm) but very poorly by PUB (Amax = 495 nm), resulting in strong limitation of the production of chemical energy by photosynthesis in their BL condition.…”
Section: Discussionmentioning
confidence: 91%
“…Growth of the cultures was monitored via raw chlorophyll fluorescence measurements using a Turner Fluorometer (Turner Designs Trilogy, model 7200, San Jose, CA, USA). The chlorophyll in vivo module (blue module model 7200-043) was used for the measurements [10]. Chlorophyll fluorescence analysis facilitates near instantaneous measurement of prime aspects of photosynthetic light capture and electron transport [35].…”
Section: Fluorescence Measurementsmentioning
confidence: 99%
“…Specific growth rate µ (d −1 ) was determined from the raw chlorophyll fluorescence measurements using the following equation [10,14]:…”
Section: Determination Of Specific Growth Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Maximum growth rates reported in Table S1 were the average exponential growth rates across all five strains in green light (0.7 day −1 max,green ; E p ) and blue light (0.5 day −1 max,blue ; E p ). Photosynthetic efficiencies were estimated following the method of Lovindeer et al (2021), assuming proportionality between growth rate (day −1 ) and the light available for growth, which was a product of the growth light intensity (μmol photons m −2 day −1 ), the absorption cross section of photosystem II (converted from Å 2 to m 2 ), and the proportion of open reaction centers available for light capture and measured by variable fluorescence (F v /F m , dimensionless). Fluorescence parameters were measured on a custom-build miniature Fluorescence Induction and Relaxation System (Maxim Gorbunov) with blue excitation.…”
Section: Model Biologymentioning
confidence: 99%